2006
DOI: 10.3892/ijo.28.6.1515
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine depletion and cell cycle manipulation in combination with HSV thymidine kinase/ganciclovir cancer gene therapy

Abstract: Abstract. We have shown earlier that polyamine biosynthesis inhibition is accompanied by cell cycle alterations that can be utilized to enhance the efficacy of herpes simplex virus thymidine kinase -ganciclovir (HSV-TK/GCV) cancer gene therapy. In the present study, we asked 1) can the activated polyamine catabolism instead of biosynthesis inhibition be utilized to enhance the efficacy of HSV-TK/GCV gene therapy, and 2) can other known cell cycle inhibitors be used to make tumor cells more sensitive to this fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…To confer cytotoxicity, cells were transfected with plasmids encoding TK (TK alone or TK‐ES), followed by GCV incubation. The efficacy of TK/GCV system depends largely on the proportion of proliferating cells, in which TK/GCV inhibits DNA replication and cell proliferation . In our study, the percentage of TK‐expressing cells at S phase was greatly increased after GCV exposure, whereas the proportion of cells at G2/M phase was significantly reduced.…”
Section: Discussionmentioning
confidence: 52%
“…To confer cytotoxicity, cells were transfected with plasmids encoding TK (TK alone or TK‐ES), followed by GCV incubation. The efficacy of TK/GCV system depends largely on the proportion of proliferating cells, in which TK/GCV inhibits DNA replication and cell proliferation . In our study, the percentage of TK‐expressing cells at S phase was greatly increased after GCV exposure, whereas the proportion of cells at G2/M phase was significantly reduced.…”
Section: Discussionmentioning
confidence: 52%
“…It has been found that primary and cultured neoplastic cells have methylation patterns which differ from the patterns of normal cells. These changes are apparent from measurements of the methylcytosine content of the DNA, which is reduced in many tumours [5][6][7][8]. DNA regions are often hypomethylated in hepatomas and leukaemias, including those of the c-myc, Ha-ras, Ki-ras, fos, Erb-A1 and bcl-2 proto-oncogenes [9,10].…”
Section: Introductionmentioning
confidence: 99%